2011
DOI: 10.1159/000323470
|View full text |Cite
|
Sign up to set email alerts
|

Severer Phenotype in Unverricht-Lundborg Disease (EPM1) Patients Compound Heterozygous for the Dodecamer Repeat Expansion and the c.202C>T Mutation in the <i>CSTB</i> Gene

Abstract: Background/Aims: Unverricht-Lundborg disease (EPM1) is caused by mutations in the cystatin B (CSTB) gene. Most patients are homozygous for the expanded dodecamer repeat mutation alleles, but 9 other EPM1-associated mutations have also been identified. We describe the clinical, cognitive and imaging characteristics of 5 Finnish EPM1 patients who are compound heterozygous for the dodecamer repeat expansion and the c.202C>T mutations. Methods: Five compound heterozygous patients and 21 patients homozygous for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Consistent with this, patients bearing one allele of R68X and the other of the usual dodecamer repeat in the cystatin B gene, show more severe pathology and clinical symptoms (Koskenkorva et al, 2011). These findings raise the question as to whether the oligomers/aggregates are cytotoxic or whether the inclusions are instead protective, as suggested by some (Kopito, 2000).…”
Section: Protein Aggregation As a Trigger For Neurodegenerative Diseasesmentioning
confidence: 76%
See 1 more Smart Citation
“…Consistent with this, patients bearing one allele of R68X and the other of the usual dodecamer repeat in the cystatin B gene, show more severe pathology and clinical symptoms (Koskenkorva et al, 2011). These findings raise the question as to whether the oligomers/aggregates are cytotoxic or whether the inclusions are instead protective, as suggested by some (Kopito, 2000).…”
Section: Protein Aggregation As a Trigger For Neurodegenerative Diseasesmentioning
confidence: 76%
“…Of note, it was reported that patients with an R68X mutation, which leads to expression of a truncated version of stefin B protein, have more severe myoclonus, drug-resistant tonic-clonic seizures and lower cognitive performance. Some were even reported to be psychotic (Koskenkorva et al, 2011). Our results, albeit obtained from experiments on cell cultures, strongly suggest that stefin B becomes more toxic when it forms aggregates and thus should be considered in future human pathological studies.…”
Section: Protein Aggregation As a Trigger For Neurodegenerative Diseasesmentioning
confidence: 99%
“…The homozygous expansion of unstable dodecamer repetition (CCCCGCCCCGCG) in the promoter 5′ untranslated region of CSTB is responsible for the most of the cases of EPM1 causing an almost homogeneous phenotype. In rare cases it can occur in compound heterozygous CSTB point and indel mutations inducing quite different phenotypes, which were recently collected by two case‐series by Koskenkorva et al, Canafoglia et al, and respective colleagues. These reports suggested a more severe phenotype in patients carrying heterozygous mutations with respect to those with homozygous promoter expansions.…”
Section: Discussionmentioning
confidence: 99%
“…The most common mutation is an expansion of unstable dodecamer repetition (CCCCGCCCCGCG) in the promoter 5′ untranslated region (usually >30 copies), which downregulates CSTB messenger RNA expression, whereas other types of mutation are rare . Among these, heterozygous compound mutations are described to induce a more severe phenotype than that of homozygous dodecameric repetition …”
mentioning
confidence: 99%
“…Although individuals with pathogenic variants in CSTB gene show similar clinical phenotype and no correlation has been found between the length of the expanded dodecamer repeat and the age of onset or disease severity, recently severer phenotype was reported in compound heterozygous individuals with repeat expansion and missense mutation. In these patients age at onset of disease is lower in compound heterozygous than homozygous patients [26]. Recently it was shown that repeat numbers have a modulating effect on the age at disease onset, myoclonus severity and cortical neurophysiology [27].…”
Section: Discussionmentioning
confidence: 99%